2022
DOI: 10.3389/fneur.2022.811092
|View full text |Cite
|
Sign up to set email alerts
|

De Novo CSNK2B Mutations in Five Cases of Poirier–Bienvenu Neurodevelopmental Syndrome

Abstract: The Poirier–Bienvenu neurodevelopmental syndrome is an autosomal dominant disorder characterized by intellectual disability and epilepsy. The disease is caused by mutations in the CSNK2B gene, which encodes the beta subunit of casein kinase II, and it has important roles in neuron development and synaptic transmission. In this study, five Chinese patients were diagnosed with Poirier–Bienvenu neurodevelopmental syndrome caused by CSNK2B mutations by whole exome sequencing. We detected four different de novo var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(12 citation statements)
references
References 22 publications
(58 reference statements)
3
9
0
Order By: Relevance
“…In view of the high prevalence of seizures in this population, all individuals with CSNK2B variants should undergo an epilepsy evaluation. Our results were similar to those in previous literature, suggesting that phenotypic heterogeneity caused by CSNK2B gene variants can range from drug-sensitive GTCS epilepsy to refractory epilepsy, with varying degrees of ID/DD (9,10,19). The seizure onset was within 6 months after birth in more than half of patients, with the first year of life in 73.68% of individuals, and almost all patients had seizures before the age of three, indicating an infantile onset and age-dependent epilepsy.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In view of the high prevalence of seizures in this population, all individuals with CSNK2B variants should undergo an epilepsy evaluation. Our results were similar to those in previous literature, suggesting that phenotypic heterogeneity caused by CSNK2B gene variants can range from drug-sensitive GTCS epilepsy to refractory epilepsy, with varying degrees of ID/DD (9,10,19). The seizure onset was within 6 months after birth in more than half of patients, with the first year of life in 73.68% of individuals, and almost all patients had seizures before the age of three, indicating an infantile onset and age-dependent epilepsy.…”
Section: Discussionsupporting
confidence: 91%
“…It is recommended that the head circumference, body growth and nutritional status be monitored regularly and that growth hormone be tested as necessary. Three patients underwent growth hormone therapy and showed good responses ( 16 , 19 ), suggesting that growth hormone supplementation is an effective treatment. Some patients have neuroimaging abnormalities without specific manifestations, which may occur at different sites.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…Selvam et al (2021) suggested that abnormal growth and height stagnation may be a phenotype of POBINDS. Yang et al (2022) and Selvam et al (2021) reported that growth hormone (GH) treatment was effective in patients with POBINDS who presented with short stature, providing evidence for the use of GH treatment for short stature due to CSNK2B variation (Yang et al, 2022). Ernst et al (2021) also reported a case of POBINDS with partial GH deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, normal expression of CSNK2B plays an important role in neuronal morphology maintenance, normal development, and synaptic transmission. Nevertheless, the pathogenesis and function of this gene variant causing POBINDS epilepsy symptoms are rarely studied and still cannot be clarified (Di Stazio et al., 2023; Yang et al., 2022), and needs to be further investigated and explored. By reviewing the HGMD (http://www.hgmd.org) and ClinVar (https://www.ncbi.nlm.nih.gov/clinvar/) databases, the variation sites of CSNK2B were heterogeneous.…”
Section: Introductionmentioning
confidence: 99%